The gravity of covid-19: an assessment of international trade policies - Ferraz, Leonardo (2022)
This study assesses the effects of the containment policies and international trade policy notifications related to the novel Coronavirus pandemic on the trade flows of 33 countries from January 2020 to June 2021. COVID-19 essential products such as medical equipment, medical supplies, personal protective equipment, and pharmaceuticals are considered in the analysis. Non-essential products such as agricultural products, among others, are also considered. The gravity model of trade is used to assess the effects of containment policies and international trade policies, which are represented by days of the month when Stay-at-home orders and Workplace Closures were imposed, the number of cases and deaths and COVID-19 trade-related notifications sent to the WTO. Our results suggest that an essential part of the policy response to the pandemic of COVID-19 lies in trade policy changes. Furthermore, these policies focused on the critical products to fight against COVID-19. The aggregated empirical gravity model showed insignificant estimates for stay-at-home requirements, workplace closures, cases, and deaths, indicating they might not be sufficient to explain the fluctuations in trade flows. On the other hand, the estimates presented by trade policies suggest that these variables can better explain trade fluctuations. The gravity model is performed disaggregated across product categories to assess the effects of different policies on different product categories. Overall, the results of the estimates of the containment policies, cases, and deaths variables seem to work as proxies for the rise in demand for goods, but their coefficients are not always statistically significant. The product disaggregated regression results reflect the demand increase for specific products. Thus the categories suffered different impacts. Pharmaceuticals presented a rise in trade volume between 2020 and 2021 and were also the category most impacted by trade policies during the pandemic. Export licenses, technical barriers to trade, and tariff policies significantly impacted the trade flows of pharmaceuticals. When importers applied these policies, the signs of the estimates resulted as positive, on the other hand, when used by exporters, the signs of the estimates are negative. It is an example of the disorderly and self-centered manner in which countries sought to secure their stock of essential goods by implementing policies that presented obstacles to exports and concomitantly sought to facilitate the importation of goods. The results for medical products not elsewhere specified and personal protection products reinforce this notion since export bans and tariff policies negatively affected trade flows for these categories. Finally, it is noted that countries have collectively sought to facilitate the flow of agricultural products by seeking to ease customs practices and export bans.